2020
DOI: 10.1055/s-0040-1710549
|View full text |Cite
|
Sign up to set email alerts
|

Topical Tranexamic Acid in Total Knee Arthroplasty: Does It Augment the Effect of the Intravenous Administration in Patients with Moderate-to-High Risk of Bleeding? A Randomized Clinical Trial

Abstract: This study aimed to compare the superimposed clinical value of topical tranexamic acid (TXA) application when it is simultaneously combined with intravenous (IV) administration versus the use of either IV TXA alone or IA TXA alone during primary total knee arthroplasty (TKA) in patients with moderate-to-high risk of bleeding. We hypothesized that the combined administration approach will result in a more adequate reduction in the perioperative blood loss and blood transfusion rate. Ninety-four patients undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Abdallah et al again showed in a trial of patients with knee arthroplasty that the best application method seemed to be a combined approach of i.v. and local tranexamic acid as it led to a significant drop of blood loss and a reduced transfusion rate [ 36 ]. Similar results could also be reproduced for knee- and hip arthroplasty showing the combined application to be superior to either topical or intravenous application [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdallah et al again showed in a trial of patients with knee arthroplasty that the best application method seemed to be a combined approach of i.v. and local tranexamic acid as it led to a significant drop of blood loss and a reduced transfusion rate [ 36 ]. Similar results could also be reproduced for knee- and hip arthroplasty showing the combined application to be superior to either topical or intravenous application [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,11,17,[21][22][23]25 Besides, the dose regime of TXA, topical or intravenous TXA, the indications of transfusion were not consistent in these studies. 1,11,12,14,17,[21][22][23]25 Hence, the above studies have reported the success of TXA in reducing blood loss and transfusion. However, what is the optimum intravenous dose of TXA to reduce perioperative blood loss remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…9 Similarly, intravenous or topical TXA in revision TKA significantly reduced the transfusion rate and blood loss. [10][11][12][13][14] However, current literature was equivocal about the optimal dosage of intravenous TXA in revision TKA, which might lead to difference in clinical outcomes. Therefore, this retrospective study aimed to analyze the different doses of intravenous TXA in terms of reducing blood loss and transfusion following revision TKA.…”
mentioning
confidence: 99%